Do Credit Default Swaps Mitigate the Impact of Credit Rating Downgrades?*. (17th October 2018) - Chava, Sudheer; Ganduri, Rohan; Ornthanalai, Chayawat
Abstract: We find that a firm's stock price reaction to its credit rating downgrade announcement is muted by 44–52% when credit default swaps (CDSs) trade on its debt. We explore the role of the CDS markets in providing information ex ante and relieving financing frictions ex post for downgraded firms. We find that the impact of CDS trading is more pronounced for firms whose debt financing is more dependent on credit ratings (e.g., those rated around the speculative-grade boundary, those with a higher number of rating-based covenants). Reductions in debt and investment, and the increase in financing costs are less severe for CDS firms than non-CDS firms following an identical credit rating downgrade. Our results suggest that CDSs mute the stock market reaction to a credit rating downgrade by alleviating the financing frictions faced by downgraded firms.